Comparison of Sonographically Evaluated Pre and Postprandial Gastric Antral Area in Type 2 Diabetics and Healthy Control Subjects - Taher, Md Abu; Sultana, Unan; Mohiuddin, AS; Sharif, Md Mofazzal; Shegufta, Farzana; Rahman, Md Towhidur; Alam, Md Muhit Ul (BIRDEM Medical Journal, 2016)
Background: Gastric motility associated with delayed gastric emptying occurs frequently in patients with diabetes mellitus. Ultrasonography play an important role by which the structure and function of the stomach can be assessed in an accurate and reproducible manner. Ultrasonographic measurement of antral cross sectional area provides a valid, cheap alternative to other costly modalities for early measurement of gastric emptying . Increased gastric antral area reflects delayed gastric emptying and gastroparesis in type 2 diabetic. Post prandial antral area is also increased in healthy subjects. But there is a significant difference in sonographically measured postprandial gastric antral area in type 2 diabetics and healthy control subjects. No such study was done previously with Bangladeshi diabetic subjects. Aims & Objective: This study was performed to compare pre and postprandial gastric antral area in type 2 diabetics and in healthy controls by ultrasonography in Bangladeshi subjects. Materials and methods: A total number of 45 consecutive type 2 diabetic subjects referred in the Department of Radiology and Imaging, BIRDEM, Dhaka, for ultrasonography of whole abdomen as routine checkup and 45 healthy subjects who underwent ultrasonography for whole abdomen for the period of one year, were enrolled in this study and were considered as group I and group II respectively. Smokers, snuff users, patients with connective tissue, cerebrovascular & endocrine diseases, receiving any drug affecting gastrointestinal motility, any previous gastriontestional tract surgery except appendisectomy were excluded from the study. All the selected subjects underwent B mode ultrasonogram of whole abdomen before and 90 mins after solid breakfast (two slices of bread and an egg). Unpaired t-test was done to compare pre and postprandial gastric antral area between type 2 diabetics and healthy controls and a P value <0.05 was taken as significant. Paired t-test was done to compare pre and postprandial gastric antral area of type 2 diabetic subjects and healthy controls and a P value <0.05 was taken as significant. Results: Majority (40.0%) of patients were in 5th decade in group I and most (31.1%) of the healthy subjects were in 4th decade. Females were predominant in both groups, which was 64.4% in group I and 66.7% in group II and female to male ratio was almost 2:1 (in the whole study subjects). In this present series it was observed that the mean preprandial gastric antral area (measured by ultrasonography) was 392.29±70.48 mm2 with range from 220 to 569 mm2 in group I and 245.27±60.59 mm2 with range from 115 to 387 mm2 in group II. On the other hand, the mean post-prandial gastric antral area (measured by ultrasonography) was 551.71±190.04 mm2 with range from 305 to 1134 mm2 and 307.82±80.87 mm2 with range from 159 to 545 mm2 in group I and group II respectively. The mean pre-prandial and post-prandial gastric antral area were significantly (P<0.05) higher in type 2 diabetic subjects and healthy control subjects. Conclusion: This study concluded that there is statistically significant difference between pre and postprandial gastric antral areas measured by B-mode ultrasonography in type 2 diabetics and healthy control Bangladeshi subjects which is similarly found in other studies. Thus ultrasonography may be routinely used to detect gastroparesis earlier in type 2 diabetics. However, whether duration of diabetes mellitus is a factor, should be studied with larger population. Birdem Med J 2015; 5(2): 82-87